Development of E-Worksheets Using Contextual Teaching and Learning to Increase Students' Critical Mathematical Thinking - Lestari Roswahyuliani; Radifan Irsaly Ruchiyat; Wawat Mugiawati; Wahyu Hidayat (Universitas Syiah Kuala, 2024)
This study aims to develop e-worksheets using contextual teaching and learning to improve students' critical mathematical thinking. The method used in developing e-worksheets was design research. The research data were obtained through validation questionnaires, student responses, and critical mathematical thinking skills tests. The research subjects used were 36 Year 10 students in one of the public high schools in West Bandung Regency. Based on the results of data analysis, the validation results obtained were 3.6 with valid criteria, and student responses about practicality obtained 'very practical' criteria with an average percentage of 86%. The product's effectiveness is said to be 'Very Good' with an average score of 80.75 from the students' post-test. The increased students' critical thinking resulted in the Moderate criteria with an N-Gain of 0.66. E-worksheets with contextual teaching and learning are feasible and can improve students' critical mathematical thinking skills on the comparison of trigonometric function.